Myocardial Strain Imaging Using Two and Three-Dimensional Speckle Tracking Echocardiography: Clinical Applications - Haque, Tuhin (Cardiovascular Journal, 2019)
Cardiac function analysis is the main focus of echocardiography. Myocardial strain & strain rate imaging have emerged as a quantitative technique to accurately estimate myocardial function. In the last decade, two dimensional speckle tracking echocardiography (2DSTE) has gained popularity as a novel technique for strain & strain rate measurement. This technique has been found clinically useful in the assessment of cardiac systolic & diastolic function. 2D strain could potentially be used to differentiate disease from nondisease segments, for identifying early subclinical changes in various pathologies and to learn more about the various strain patterns indicative of specific disease types. A large number of studies have evaluated the role of 2DSTE in predicting the response to cardiac resynchronization therapy in patients with severe heart failure. Emerging areas of applications of 2DSTE include prediction of rejection in heart transplant patients, early detection of cardiotoxicity in patients receiving chemotherapy for cancer and effect of intracoronary injection of bone marrow stem cells on left ventricular function in patients with acute myocardial infarction. However, 2D imaging methods have limitations in assessing three dimensional (3D) cardiac motion. Experimental studies and clinical investigations revealed the reliability and feasibility of 3DSTE-derived data. In this review, the methodology, validation, and clinical application of both 2D &3DSTE have been discussed. Cardiovasc. j. 2019; 11(2): 167-182